The genome sequence of Glossophaga mutica (Chiroptera, Phyllostomidae, Glossophaginae; Merriam, 1898) [version 1; peer review: 2 approved] - Erich D. Jarvis; Bonhwang Koo; Melissa R. Ingala; Laramie L. Lindsey; Philge Philip; Nancy B. Simmons; Emma C. Teeling; Myrtani Pieri; Linelle Abueg; Giulio Formenti; Larry N. Singh; Ning Zhang; et al. (Wellcome Open Research)
We present a genome assembly from an individual female Glossophaga mutica (Chordata; Mammalia; Chiroptera; Phyllostomidae). The genome sequence is 2.13 in span. The majority of the assembly is scaffolded into 32 chromosomal pseudomolecules, with the X sex chromosome assembled.